2021
DOI: 10.1186/s12885-021-08984-1
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic leakage after pelvic lymphadenectomy for cervical cancer: a retrospective case-control study

Abstract: Background The study aims to evaluate the clinical features and management of postoperative lymphatic leakage (PLL) in patients with cervical cancer who received pelvic lymphadenectomy. Methods This retrospective study screened consecutive patients with cervical cancer (stage Ia2-IIb). Results Among 3427 cases screened, 63 patients (1.8%) were diagnosed with PLL, which manifested as persistent abdomina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Thus, clinical management modalities have been mainly focused on conservative treatment and watchful waiting [ 19 ] . The traditional way of dealing with a persistent high volume (more than 50 mL/day) drainage was to keep the drainage tube till the drainage volume decreased to lower than 50 mL/day [ 20 ] . However, it is unclear if this is the best way to manage the high‐volume lymphatic leakage by leaving the drain for an extended period, or on the contrary, the lower intra‐abdominal pressure produced by the gravity drain may have potentially perpetuated an otherwise small lymph leak, leading to a persistent lymphatic leakage [ 7 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, clinical management modalities have been mainly focused on conservative treatment and watchful waiting [ 19 ] . The traditional way of dealing with a persistent high volume (more than 50 mL/day) drainage was to keep the drainage tube till the drainage volume decreased to lower than 50 mL/day [ 20 ] . However, it is unclear if this is the best way to manage the high‐volume lymphatic leakage by leaving the drain for an extended period, or on the contrary, the lower intra‐abdominal pressure produced by the gravity drain may have potentially perpetuated an otherwise small lymph leak, leading to a persistent lymphatic leakage [ 7 ] .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the duration median was 8, 3, or 7 days in hepatobiliary surgery, gastrointestinal surgery, and urological surgery. For gynecological surgery patients with chylous leakage cured by TPN alone, the median was 15 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16) days (60). The median for days of drainage was 3 (1-21) days (3 cases discharged with a drainage tube on day 1 of intervention and 1 on day 2) in the present study under a similar condition.…”
Section: Discussionmentioning
confidence: 99%
“…We found no relevant reports on the analysis of factors associated with effective postintervention outcomes. However, it was reported that lower hemoglobin is associated with a higher incidence rate of CL ( 14 ), which may predict that lower hemoglobin probably influences the effects of oral nutritional interventions. Our analysis of post-operative hemoglobin on intervention outcomes may inform future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation